The Prophet Jesus - Bakour Mohamad, Bachar (Nouresham Book Center, Al-Fatih Islamic nstitute, 2019)
Jesus, the Messiah (‘Îsa in Arabic), a Spirit and Word from Allah. He was the son of Virgin Mary, daughter of Joachim (Imran), the last Prophet sent to the Children of Israel. The lineage of Jesus is the same as his mother's, since he was born miraculously without a father (i.e. of virgin birth). Paradoxically, the New Testament, despite referring to his miraculous birth [Matthew1:18; Luke1: 34], provides contradictory ...